Comparison of Different Materials Used in The Preparation Of Household Bioplastics and Evaluation of a Mixture of Animal Gelatin and Cornstarch - Kamar Shayah; Joseph Shenekji; Durra Balt; Siran Arabanian; Joudy Awyga; Sawsan Salloum (Syrian Journal for Science and Innovation)
The harmful environmental impacts of plastic materials used in packaging have necessitated the adoption of environmentally friendly bioplastics as an alternative to petroleum-derived plastics due to their unique properties. While most bioplastics are starch-based, they are not without shortcomings, thus requiring improvements in their mechanical and chemical properties. In this study, experiments were conducted with various materials to produce bioplastics to evaluate the effect of these materials on the final product's consistency. In the final experiment, the combination of corn starch and animal gelatin was tested for its impact on the mechanical and chemical properties of the final product. The impact of incorporating animal gelatin into corn starch on the chemical and mechanical properties of the end product was examined. The resulting product exhibited improved texture and tensile strength compared to membranes made from starch alone. Microscopic analysis revealed that the final product had a denser texture and more granular appearance than the starch-based products. By evaluating the product characteristics, it is evident that this material can be utilized for household food packaging due to its favorable tensile and mechanical properties at a cost-effective price. Several bioplastic mixtures were compared in this study. The results indicate that the optimal bioplastic composition consists of a blend of corn starch 2.6% and animal-derived gelatin 5.2%. This hybrid material demonstrated superior mechanical properties, biodegradability, and overall functionality compared to the pure constituent components. The synergistic effects observed in the corn starch-gelatin bioplastic suggest that this formulation represents a promising sustainable alternative to traditional petroleum-based plastics. It can be used and manufactured domestically and industrially, and it showed long durability and decent expiration before degradation. Further research is recommended to explore the scalability and potential industrial applications of this innovative bioplastic.